1995
DOI: 10.3109/10641969509037420
|View full text |Cite
|
Sign up to set email alerts
|

Pressor Effect of Recombinant Human Erythropoietin: Results of Ambulatory Blood Pressure Monitoring and Home Blood Pressure Measurements

Abstract: We investigated whether treatment of anemic hemodialysis patients with a low dose of recombinant human erythropoietin (erythropoietin) for a short period would increase their blood pressure. Ambulatory blood pressure monitoring and home blood pressure measurements were used to detect minute increase in blood pressure. Thirty-two patients with a hematocrit of 25% or less received erythropoietin at the dose of 4500 IU/week, by the intravenous route for 8 weeks. Erythropoietin increased the hematocrit from 20.9 +… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

1997
1997
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(3 citation statements)
references
References 41 publications
1
2
0
Order By: Relevance
“…One unifying factor has been a lack of a significant reduction in cardiac output in patients in whom BP increases, which may be due to abnormal cardiovascular autoregulation in these patients. The lack of effect of epoetin alfa on BP in this trial is consistent with other reports [39], which found that with a dose of 4500 IU/week there was no observed pressor effect of epoetin alfa on clinic BP measurements, but demonstrable differences were detected by continuous ambulatory BP measurement. In this trial, we did not employ ambulatory BP measurements, and so cannot provide evidence for or against an ESA effect on continuous ambulatory BP measurements.…”
Section: Discussionsupporting
confidence: 92%
“…One unifying factor has been a lack of a significant reduction in cardiac output in patients in whom BP increases, which may be due to abnormal cardiovascular autoregulation in these patients. The lack of effect of epoetin alfa on BP in this trial is consistent with other reports [39], which found that with a dose of 4500 IU/week there was no observed pressor effect of epoetin alfa on clinic BP measurements, but demonstrable differences were detected by continuous ambulatory BP measurement. In this trial, we did not employ ambulatory BP measurements, and so cannot provide evidence for or against an ESA effect on continuous ambulatory BP measurements.…”
Section: Discussionsupporting
confidence: 92%
“…For example, whereas routine BP monitoring failed to demonstrate changes in BP with the administration of erythropoietin (22), ABPM was able to detect a rise in overall BP with just 13 patients (23). ABPM was also more sensitive in detecting a rise in BP with erythropoietin than was home BP monitoring (24). We have exploited the reproducibility and sensitivity of ABPM in detecting antihypertensive effects of water‐soluble antihypertensive drugs administered to hemodialysis patients three times weekly using only a small number of subjects (25,26).…”
Section: Comparison Of Bp Measurement Methodsmentioning
confidence: 99%
“…For example, whereas routine BP monitoring failed to demonstrate changes in BP with the administration of erythropoietin (44), ABPM was able to detect an increase in overall BP with just 13 patients (45). When ABPM was compared to home BP monitoring, again ABPM was found to be more sensitive in detecting an increase in BP with erythropoietin (46). We have exploited the reproducibility and sensitivity of ABPM in detecting the effects of antihypertensive drugs administered to hemodialysis patients three times a week using only a small number of subjects (47,48).…”
Section: Information Provided By Ambulatory Bp Monitoringmentioning
confidence: 99%